Farm Manager - Ahmad, Jibreen Daghameen; Mohammad, Mahmoud Hijaz; Tariq, Radi Asedih (My University, 2017)
Farm Manager is basically a web application with a co-application for android mobiles. This product is meant to Provide helpful tools for simple farmers and agricultural companies to manage their farms by helping them to follow up each and every process of the agricultural operations from the start of preparing the land and cultivating both plants and animals, down to production processes, ending with collecting and selling the products. It will also help the owner and/or the admin to take the right decision by sending scheduled hints to the owner's inbox of information collected from specialists in the agricultural fields. Farm Manager was developed using web programing languages like HTML5, PHP, and CSS3. And for the android app we used Java and xml languages. And we used MySQL database on Wamp local server